UPAYA MENINGKATKAN KUALITAS AIR WADUK DIPONEGORO PADA DAS KRENGSENG, SEMARANG - Grace Lucy Secioputri; Rahmat Kurniawan; Suseno Darsono; Priyo Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
This paper will explain how to maintain and improve water quality in Diponegoro reservoir. Krengseng watershed‘s area are Banyumanik sub-district and Tembalang sub-district which is Diponegoro reservoir catchment area that water influent to reservoir should have wastewater quality fit with the quality of wastewater domestic standard. Therefore, it needed domestic wastewater sewerage system and treatment plant in Krengseng watershed area. Domestic wastewater sewerage system and treatment plants design required some data such as quantity of domestic wastewater, water pollutants, population, and also overall site layout that would be used to design the domestic wastewater sewer system. To analyzed and sewer system design, we can used EPA SWMM 5.0 with small bore sewer as the main idea for sewer system. Specification that should be fulfilled are minimum pipe slope more than 0.006, flow rate between 0.6-3 m/s, and water flow quantity in pipe between 0.2-0.8 of pipe diameter. For treatment plants used septic tank as primary treatment and anaerobic filter as secondary treatment. Total cost for this design are planned Rp 133.819.636.500,00 with construction duration for one year and ten months.